2016
DOI: 10.1007/s00253-016-7945-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bacterial community composition in response to uranium levels in sediment samples of sacred Cauvery River

Abstract: Global industrialization is a major cause of effluent discharge from industries up to alarming concentrations. Especially, uranium concentrations in water bodies are of great concern, as its radioactivity significantly affects the persistent diversity of microbiota. Recently, continuous application of pesticides in the agricultural lands and accumulation of quartz that enter the Cauvery River has significantly increased the concentration of uranium (U) and other heavy metals. To perceive the impact of uranium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…; Supporting Information Material S4). Such shifts in abundant and rare taxa have previously been observed in uranium enriched soils (Suriya et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Supporting Information Material S4). Such shifts in abundant and rare taxa have previously been observed in uranium enriched soils (Suriya et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…To date, a number of microbial surveys in uraniumenriched soils and sediments have been reported Rastogi et al, 2010;Dhal et al, 2011;Islam and Sar, 2011;Mondani et al, 2011;Suriya et al, 2016). These studies demonstrate that taxonomically diverse microbial communities survive in uranium-enriched environments.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, Chloroflexi may contribute to the slow dissipation of TCS observed in the microcosms (Chapter 4). In accordance with our results, Suriya et al (2017) found that the relative abundance of Firmicutes was dramatically reduced in sediment samples collected from a contaminated area. It should be noted that TCS significantly reduced the relative abundance of Bacteroidetes at 8 µg/g dw, suggesting that Bacteroidetes were very sensitive to TCS.…”
Section: Discussionsupporting
confidence: 92%
“…Thus sulfate-reducing bacteria producing sulfide could facilitate uranium reduction by liberating adsorbed U(VI) and reducing the metal. When a [116]. From all of these examples, uranium reduction was observed abiotically, extracellularly, periplasmically, cytoplasmically and in mixed biotic-abiotic systems and the mechanisms examined reveal a diverse array of uranium reduction reactions from a diverse set of bacteria ( Table 2 & Table 3).…”
Section: Theory Calculations Have Also Indicated a U(v) Intermediate mentioning
confidence: 99%